The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fped.2020.00438
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Intussusception Diagnosed by Total Colonoscopy in a Child: A Case Report

Abstract: Background: Ileocolic intussusception is the most common form of intussusception in children. Intussusception in the appendix or cecum without a lead point in a child is very rare and was found with total colonoscopy (TCS) and computed tomography. Case Presentation: A 9 year-old boy was admitted to our hospital with fever, vomiting, and two episodes of bloody diarrhea. Inflammatory bowel disease was suspected; TCS was performed and revealed intussusception whose advanced region was in the cecum. The diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…About one-fifth of our patients had a PLP. This finding is compa-rable to the report of one study from Saga, Japan which reported that in approximately 25 percent of cases of intussusception in older children, there is an underlying disease that causes development of a pathologic lead point for the intussusception [26]. However, in infants and younger children, the incidence of intussusception is less.…”
Section: Discussionsupporting
confidence: 71%
“…About one-fifth of our patients had a PLP. This finding is compa-rable to the report of one study from Saga, Japan which reported that in approximately 25 percent of cases of intussusception in older children, there is an underlying disease that causes development of a pathologic lead point for the intussusception [26]. However, in infants and younger children, the incidence of intussusception is less.…”
Section: Discussionsupporting
confidence: 71%